EXPLORING BEGINNING EFL TEACHER IN MAKING LESSON PLAN FOR FIRST YEAR STUDENTS OF PUBLIC SENIOR HIGH SCHOOL IN MAKASSAR - Yunitari Mustikawati (ELT Worldwide: Journal of English Language Teaching, 2019)
This study aims at exploring the beginning EFL teacher in making learning objective, selecting learning materials, and assessment used in learning, and discovering the problems and solutions of the beginning EFL teacher. This study is qualitative research with a case study. Data sources of the study were one beginning EFL teacher of SMAN A (pseudonym), the Vice Principal of SMAN A, and the Head of MGMP Makassar. Data were collected by employing observation, interview, questionnaire, and documentation. The results of the study reveal that the beginning EFL teacher has problem in formulating clear learning objective and in using appropriate assessment to students’ achievement. However, he has adequate knowledge of selecting the materials from the easiest to the most challenging one. The solutions to overcome the problems of the beginning EFL teacher are to provide supervisor (superintendent) with the same discipline in school, assign qualified experienced teacher as mentor teacher to guide the beginning EFL teacher in his first year of teaching, and assign the beginning EFL teacher to join MGMP and attend its monthly meetings as a compulsory activity.